Synchronization among activities in a workflow using extended workflow Petri nets - Kotb, Yehia; Badreddin, Essameddin (Seventh IEEE International Conference on E-Commerce Technology workshops 2005, 2005)
To maximize throughput in workflow systems concurrency is required. On the other hand concurrency must be controlled especially in systems in which a set of tasks can not serve more than one activity at a time constituting a critical section. This paper introduces an extended workflow Petri net model to deal with synchronization among activities in workflows which include critical sections and which the validity of resource tokens is subject to real time constraints. The paper also addresses the soundness property of the proposed extended workflow Petri net.
Gesehen am 16.12.2019